2005
DOI: 10.1159/000088343
|View full text |Cite
|
Sign up to set email alerts
|

Arterial Wall Response to ex vivo Exposure to Oscillatory Shear Stress

Abstract: Background: The aim of this study was to analyze the arterial wall response to plaque-prone hemodynamic environments, known to occur mainly in areas of arterial trees such as bifurcations and branching points. In these areas, the vasculature is exposed to cyclically reversing flow that induces an endothelial dysfunction predisposing thus arteries to local development of atherosclerotic plaques. Methods: We used an ex vivo perfusion system that allows culturing arterial segments under different hemodynamic cond… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
47
1
4

Year Published

2007
2007
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 67 publications
(55 citation statements)
references
References 55 publications
3
47
1
4
Order By: Relevance
“…Details on ex vivo arterial support system have been given earlier. 14 The arterial segments were perfused for 24 h with M199-EBS (Amersham) containing 5% fetal calf serum. The medium was constantly gas-infused with 5% CO 2 and 95% air.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Details on ex vivo arterial support system have been given earlier. 14 The arterial segments were perfused for 24 h with M199-EBS (Amersham) containing 5% fetal calf serum. The medium was constantly gas-infused with 5% CO 2 and 95% air.…”
Section: Methodsmentioning
confidence: 99%
“…Protein expression and gelatinolytic activity were assessed using immunoblot and zymography techniques, respectively, as described earlier. 14 Protein was extracted from the samples with a Brij-35 lyses buffer (50 mmol/l Tris pH 7.5, 1 mol/l NaCl, 2 mol/l Urea, 0.1% Brij-35, and 1 protease inhibitor cocktail (Roche)). 20 µg of protein was subjected to electrophoresis, and then transferred to a nitrocellulose filter (Amersham).…”
Section: Methodsmentioning
confidence: 99%
“…Furthermore, Dardik et al [53] has revealed that vascular response seems to be significantly influenced by the exact type of shear stress. For instance, matrix metalloproteinase up-regulation, higher proliferation of cells, and a pro-inflammatory environment can be caused by oscillatory shear stress [54]. On the other hand, normal dilatation and endothelial stability are the outcomes of laminar shear stress [55].…”
Section: Endothelium Dysfunction and Avf Maturationmentioning
confidence: 99%
“…Oscillatory shear stress induces VSMC migration by increasing the expression of MMP-2 and MMP-9 and decreasing plasminogen activator inhibitor-1 (PAI-1) expression [134,135]. In vascular grafts, disturbed flow provides favourable conditions for VSMC proliferation with low shear stress, which may explain, in part, why intimal hyperplasia and atherosclerotic lesions develop preferentially in slow-flow regions [136].…”
mentioning
confidence: 99%